2021
DOI: 10.3390/en14133908
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pure Oxygenated Biofuels on Efficiency and Emissions in a Gasoline Optimised DISI Engine

Abstract: The negative impact of transport on climate has led to incentives to increase the amount of renewable fuels used in internal combustion engines (ICEs). Oxygenated, liquid biofuels are promising alternatives, as they exhibit similar combustion behaviour to gasoline. In this article, the effect of the different biofuels on engine efficiency, combustion propagation and emissions of a gasoline-optimised direct injected spark ignited (DISI) engine were evaluated through engine experiments. The experiments were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…In the current study, only for the highest engine load were the HC and CO emissions very close for the isobutanol binary blend and base gasoline. Such an increase might be caused by significant difference in fuel properties, mainly the higher heat of evaporation and lower vapor pressure of isobutanol, especially at lower engine load/speed conditions [85]. In multiple studies focused on alcohol blends used in SI engines, lower HC and CO emissions were reported [86,87].…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, only for the highest engine load were the HC and CO emissions very close for the isobutanol binary blend and base gasoline. Such an increase might be caused by significant difference in fuel properties, mainly the higher heat of evaporation and lower vapor pressure of isobutanol, especially at lower engine load/speed conditions [85]. In multiple studies focused on alcohol blends used in SI engines, lower HC and CO emissions were reported [86,87].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a better insight into the effect of neat methanol on PM emissions is essential. Larsson et al [17] observed that oxygenated fuels tend to decrease particle emissions thanks to their chemical structure, which inhibits the formation of soot precursors and increases post-oxidation. Nevertheless, the formation of particles also depends on the physical properties of the fuel such as the volatility.…”
Section: Introductionmentioning
confidence: 99%
“…Low volatility, in fact, can cause pool fires where particles are formed. On the other hand, Svensson et al [18] observed that methanol has a non-sooting behavior and, hence, particles measured at the exhaust of a pure methanol-fueled engine could be due to sources other than the fuel such as oil leakage [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have been reported about the implementation of OFC in GDI engines or dual-injection SI engines. However, Gasoline Direct Injection (GDI) technology has become the mainstream of SI engines in academia and industry [27][28][29][30][31][32][33][34][35]. In 2005, an advanced technology named dual-injection was commercially applied to SI engines by Toyota [36].…”
Section: Introductionmentioning
confidence: 99%